Quality Control Pada Sekolah Tinggi Ilmu Ekonomi (STIE) NOBEL Indonesia Makassar - ., Mariah (Eklektika, 2013)
This study aims at discovering the description on quality control on the input phase, in this case studentsâ input and curikulum, the proses phase which discussed on the learning process, and the output phase of the graduates of the collage of Nobel Indonesia in Makassar. The results showed that the Quality Control at Sekolah Tinggi Ilmu Ekonomi (STIE) Nobel Indonesia Makassar review of: 1. Input: (a) Students include recruitment, extracurricular activities, services, counseling, (b) the input curriculum characterized by the structure of the curriculum, curriculum coverage, relevance of curriculum, semester credit unit load, curriculum integration, and flexibility of the curriculum. 2. The process in question is the learning plan, the implementation of learning, assessment of learning outcomes, monitoring learning and teaching development. 3. Output that discusses qualifications attitudes, knowledge and skills. Keywords: Quality Control